Juridical Analysis of Law Number 17 of 2023 Concerning Health on Legal Protection for Medical and Health Personnel - Nurchasanah, Nurchasanah; Sakti, Muthia; Adhi Nugroho, Andriyanto (Asian Journal of Social and Humanities, 2025)
The enactment of Law Number 17 of 2023 concerning Health marks a new era in Indonesia’s legal framework through an omnibus approach aimed at harmonizing and consolidating overlapping health regulations. This study examines the legal protection of medical and health personnel in performing their professional duties as stipulated in the new Health Law and its implementing regulation, Government Regulation Number 28 of 2024. Using a normative juridical research method, the study relies on secondary legal materials, including legislation, legal doctrines, and scholarly literature. The findings indicate that Law No. 17/2023 repeals eleven previous health-related statutes and introduces a more comprehensive legal framework to strengthen healthcare governance and ensure professional accountability. The law expands the scope of legal protection for medical personnel by including standards of professional ethics, service quality, and patient health needs, which were not explicitly covered in earlier laws. Moreover, the regulation outlines the responsibilities of central and local governments, as well as healthcare facility administrators, in providing preventive and responsive legal protection. The study concludes that the 2023 Health Law represents a significant legal reform that reinforces the state’s constitutional duty to ensure fairness, legal certainty, and the protection of both healthcare providers and patients, thereby promoting a just, ethical, and sustainable health system in Indonesia.